2017
DOI: 10.5455/medarh.2017.71.48-51
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Clinical and Radiological Parameters at Knee Osteoarthritis

Abstract: Introduction:Osteoarthritis (OA) or arthrosis represents an inflammatory disease of joints that develops as a result of interaction of mechanical and biological parameters. With disease development, degenerative changes on joint cartilage can be noticeable that affect and cause pathological changes on other parts of a joint resulting in pain and dysfunction of a joint. A. E. Garrod in 1907 described osteoarthritis as a special clinical entity and separated it from a rheumatoid arthritis. OA is characterized wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 10 publications
(17 reference statements)
2
3
0
Order By: Relevance
“…Our study found no correlation between either the WOMAC score or KSS score when compared to the severity of the radiographs as classified by either KL or Ahlbäck ( Figure 7 ). This is in keeping with the results found by Talic-Tanovi et al and Szebenyi et al However, we did not, find a correlation between subchondral sclerosis and pain as found by Szebenyi et al [ 8 , 16 , 19 ]. This is in contrast to Kocak et al, who found that higher patients with higher-grade radiological gradings suffer from more severe clinical features [ 17 ].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Our study found no correlation between either the WOMAC score or KSS score when compared to the severity of the radiographs as classified by either KL or Ahlbäck ( Figure 7 ). This is in keeping with the results found by Talic-Tanovi et al and Szebenyi et al However, we did not, find a correlation between subchondral sclerosis and pain as found by Szebenyi et al [ 8 , 16 , 19 ]. This is in contrast to Kocak et al, who found that higher patients with higher-grade radiological gradings suffer from more severe clinical features [ 17 ].…”
Section: Discussionsupporting
confidence: 93%
“…In our study, the vast majority (92%) of participants were female. This correlates to previous studies that showed a higher incidence of OA in females [ 14 , 19 ]. Western Ontario and McMaster Osteoarthritis Index (WOMAC) score consist of three subsections: Pain, stiffness and function.…”
Section: Discussionsupporting
confidence: 92%
“…The proposed scheme should be suitable for the description of DDD in any large animal and human IVD. Use of this scheme may further identify that like degenerative arthritic changes in OA and RA [ 196 , 197 , 198 , 199 , 200 , 201 , 202 , 203 ], DDD displays a spectrum of degenerative features and several sub-types of DDD are likely to be identified in the future when sufficient data is collected for critical evaluation. However for such a development to occur one must have a reliable, discriminative scoring scheme capable of evaluating the relative importance of each of the listed degenerative features of DDD.…”
Section: Discussionmentioning
confidence: 99%
“… 20 – 23 However, subchondral bone in OA is subjected to a decrease rather than an increase in bone stiffness. 24 , 25 In addition, uncoupled bone remodelling by osteoclasts and osteoblasts in subchondral bone contributes to cartilage degeneration, which gradually results in TMJ-OA lesions. 13 , 26 …”
Section: Introductionmentioning
confidence: 99%